The PerformanceStat Potential : A Leadership Strategy for Producing Results - Behn, Robert D. (Book collections on Project MUSE., 2014)
"Here, Harvard leadership and management guru Robert Behn analyzes the leadership behaviors at the core of PerformanceStat to identify how they work to produce results. He examines how the leaders of a variety of public organizations employ the strategy-the way the Los Angeles County Department of Public Social Services uses its DPSSTATS to promote economic independence, how the City of New Orleans uses its BlightStat to eradicate blight in city neighborhoods, and what the Federal Emergency Management Agency does with its FEMAStat to ensure that the lessons from each crisis response, recovery, and mitigation are applied in the future"--EBL